mTERF8, a Member of the Mitochondrial Transcription Termination Factor Family, Is Involved in the Transcription Termination of Chloroplast Gene psbJ - Xiong, Hai-Bo (Plant Physiol, 2020)
Members of the mitochondrial transcription terminator factor (mTERF) family, originally identified in vertebrate mitochondria, are involved in the termination of organellular transcription. In plants, mTERF proteins are mainly localized in chloroplasts and mitochondria. In Arabidopsis (Arabidopsis thaliana), mTERF8/pTAC15 was identified in the plastid-encoded RNA polymerase (PEP) complex, the major RNA polymerase of chloroplasts. In this work, we demonstrate that mTERF8 is associated with the PEP complex. An mTERF8 knockout line displayed a wild-type–like phenotype under standard growth conditions, but showed impaired efficiency of photosystem II electron flow. Transcription of most chloroplast genes was not substantially affected in the mterf8 mutant; however, the level of the psbJ transcript from the psbEFLJ polycistron was increased. RNA blot analysis showed that a larger transcript accumulates in mterf8 than in the wild type. Thus, abnormal transcription and/or RNA processing occur for the psbEFLJ polycistron. Circular reverse transcription PCR and sequence analysis showed that the psbJ transcript terminates 95 nucleotides downstream of the translation stop codon in the wild type, whereas its termination is aberrant in mterf8. Both electrophoresis mobility shift assays and chloroplast chromatin immunoprecipitation analysis showed that mTERF8 specifically binds to the 3′ terminal region of psbJ. Transcription analysis using the in vitro T7 RNA polymerase system showed that mTERF8 terminates psbJ transcription. Together, these results suggest that mTERF8 is specifically involved in the transcription termination of the chloroplast gene psbJ.